Sulfur metabolism in phototrophic organisms - Hell, Rüdiger (Advances in photosynthesis and respiration, 2008)
Sulfur is one of the most versatile elements in life. This book provides, for the first time, in-depth and integrated coverage of the functions of sulfur in phototrophic organisms including bacteria, plants and algae. It bridges gaps between biochemistry and cellular biology of sulfur in these organisms, and of biology and environments dominated by them. The book therefore provides a comprehensive overview of plant sulfur relations from genome to environment.